L-Arginine Pathway Metabolites Predict Need for Intra-operative Shunt During Carotid Endarterectomy. Issue 6 (December 2016) - Szabo, P.; Lantos, J.; Nagy, L.; Keki, S.; Volgyi, E.; Menyhei, G.; Illes, Z.; Molnar, T.
Abstract : Objective/Background: Asymmetric dimethylarginine (ADMA) inhibits nitric oxide (NO) synthesis and is a marker of atherosclerosis. This study examined the correlation between pre-operativel -arginine and ADMA concentration during carotid endarterectomy (CEA), and jugular lactate indicating anaerobic cerebral metabolism, jugular S100B reflecting blood–brain barrier integrity, and with factors of surgical intervention. Methods: The concentration ofl -arginine, ADMA, and symmetric dimethylarginine was measured in blood taken under regional anaesthesia from the radial artery of 55 patients prior to CEA. Blood gas parameters, concentration of lactate, and S100B were also serially measured in blood taken from both the radial artery and the jugular bulb before and after carotid clamping, and after release of the clamp. To estimate anaerobic metabolism, the jugulo-arterial ratio of CO2 gap/oxygen extraction was calculated. Results: Positive correlation was found between pre-operative ADMA levels and the ratio of jugulo-arterial CO2 gap/oxygen extraction during clamp and reperfusion ( p  = .005 and p  = .01, respectively). An inverse correlation was found between the pre-operativel -arginine concentration and jugular lactate at each time point (both p  = .002). The critical pre-operative level ofl -arginine was determined by receiver operator curve analysis. Ifl -arginine was below the cutoff value of 35 μmol/L, jugular S100B concentration was higher 24 h post-operatively ( p  = .03), and jugular lactate levels were increased during reperfusion ( p  = .02). The median pre-operative concentration ofl -arginine was lower in patients requiring an intra-operative shunt than in patients without need of shunt (median: 30.3 μmol/L [interquartile range 24.4–34.4 μmol/L] vs. 57.6 μmol/L [interquartile range 42.3–74.5 μmol/L]; p  = .002). Conclusion: High pre-operative ADMA concentration predicts poor cerebral perfusion indicated by elevated jugulo-arterial CO2 gap/oxygen extraction. Low pre-operativel -arginine concentration predicts the need for a shunt. The inverse correlation between pre-operativel -arginine concentration and both jugular lactate and S100B during carotid clamping suggests a protective role of the NO donorl -arginine.